Toward Cleavable Metabolic/pH Sensing "Double Agents" Hyperpolarized by NMR Signal Amplification by Reversible Exchange. Issue 42 (29th June 2018) - Kidd, Bryce E.; Mashni, Jamil A.; Limbach, Miranda N.; Shi, Fan; Chekmenev, Eduard Y.; Hou, Yuqing; Goodson, Boyd M.
Abstract: We show the simultaneous generation of hyperpolarized 13 C‐labeled acetate and 15 N‐labeled imidazole following spin‐relay of hyperpolarization and hydrolysis of the acetyl moiety on 1– 13 C‐ 15 N2 ‐acetylimidazole. Using SABRE‐SHEATH (Signal Amplification by Reversible Exchange in SHield Enables Alignment Transfer to Heteronuclei), transfer of spin order occurs from parahydrogen to acetylimidazole 15 N atoms and the acetyl 13 C site (≈263‐fold enhancement), giving rise to relatively long hyperpolarization lifetimes at 0.3 T ( T 1 ≈52 s and ≈149 s for 13 C and 15 N, respectively). Immediately following polarization transfer, the 13 C‐labeled acetyl group is hydrolytically cleaved to produce hyperpolarized 13 C‐acetate/acetic acid (≈140‐fold enhancement) and 15 N‐imidazole (≈180‐fold enhancement), the former with a 13 C T 1 of ≈14 s at 0.3 T. Straightforward synthetic routes, efficient spin‐relay of SABRE hyperpolarization, and facile bond cleavage open a door to the cheap and rapid generation of long‐lived hyperpolarized states within a wide range of molecular targets, including biologically relevant carboxylic acid derivatives, for metabolic and pH imaging. Abstract : A "spin‐spy" with two masters : While bound to a catalyst, a molecular "double agent" borrows nuclear spin order from parahydrogen. The molecule's more‐distant 13 C spin is polarized via "spin relay" from a 15 N spin closer to the catalyst, exploiting scalar coupling. Hydrolytic cleavage yields two separate hyperpolarized agents— 13 C‐acetate/acetic acid and 15 N2 ‐imidazole—the enhanced NMR signals of which can report on metabolism and local pH, respectively.